2021
DOI: 10.1002/adfm.202009803
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Screening for Phase‐Change Memory Materials

Abstract: Phase change memory (PCM) is an emerging non-volatile data storage technology concerned by the semiconductor industry. To improve the performances, previous efforts have mainly focused on partially replacing or doping elements in the flagship Ge-Sb-Te (GST) alloy based on experimental "trialand-error" methods. Here, the current largest scale PCM materials searching is reported, starting with 124 515 candidate materials, using a rational highthroughput screening strategy consisting of criteria related to PCM ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 96 publications
0
34
0
1
Order By: Relevance
“…Other compound PCMs such as sesqui-chalcogenides (e.g., Sb 2 Te 3 ) [19] and tetrelschalcogenides (e.g., GeTe or SnSe 2 ) [20] have also been investigated. Very recently, Liu et al [21] have systematically filtered out 50 potential PCMs similar to GST from more than 12 000 inorganic crystal structures by a four tiers of screening strategy, but all with narrow bandgaps (<1 eV). Thus, developing widerbandgap PCMs with large refractive index change is of great interest in the long run.…”
mentioning
confidence: 99%
“…Other compound PCMs such as sesqui-chalcogenides (e.g., Sb 2 Te 3 ) [19] and tetrelschalcogenides (e.g., GeTe or SnSe 2 ) [20] have also been investigated. Very recently, Liu et al [21] have systematically filtered out 50 potential PCMs similar to GST from more than 12 000 inorganic crystal structures by a four tiers of screening strategy, but all with narrow bandgaps (<1 eV). Thus, developing widerbandgap PCMs with large refractive index change is of great interest in the long run.…”
mentioning
confidence: 99%
“…The recent work of Y.‐T. Liu demonstrated that the melting point is positively correlated to the cohesive energy ( E c ) and low E c values tend to exhibit the low energy cost for PCM applications 10 . Hence, we believe that it is highly likely that the E c of GST could be reduced by In doping, which promotes the energy efficiency in the related devices.…”
Section: Resultsmentioning
confidence: 98%
“…However, no dopants can achieve fast speed, low power consumption, and long life time at the same time. A recent publication provided a screening strategy of PCM materials theoretically that good comprehensive performances with balanced speed, data retention and power consumption could be expected by bond‐angle deviation ( D BAD ), the Born effective charge ( Z *), and cohesive energy ( E c ), indicating that there would be a kind of phase‐change material that can achieve the above properties at the same time 10 . A GST with good performances is developed from the complement of GeTe with Sb 2 Te 3 octahedrons.…”
Section: Introductionmentioning
confidence: 99%
“…Materials Acceleration Platforms (MAP) [ 19 ] are an emerging paradigm to accelerate the discovery of materials and especially functional nanomaterials. The reduced timeline of accelerated nanomaterial development is facilitated by the convergence of High-Throughput Computational (HTC) screening [ 53 , 54 , 55 , 56 ] with improved computations using ab initio codes for simulations [ 57 , 58 ] of electronic structure, materials properties predictions [ 59 , 60 , 61 ], automation [ 62 ], and robotic [ 63 , 64 , 65 ] systems for chemistry laboratories, using scientific AI in materials science [ 66 ] and the diversity of machine learning methods adapted to material science and areas of physics and chemistry.…”
Section: Brief Review Of Nanomaterials Discovery Approachesmentioning
confidence: 99%